Supervisi Klinis Kepala Sekolah Dalam Meningkatkan Kompetensi Pedagogi Guru Di Madrasah Aliyah Swasta Al-Washliyah 22 Tembung - Muhammad Khalid Pay Hasibuan; Muhammad Rifai (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Clinical Supervision of Principals in Improving Teachers' Pedagogical Competence at Al-Washliyah Private Aliyah Madrasah 22 Tembung This research discusses the role of clinical supervision by the head of the madrasah in improving the pedagogical competence of teachers at Madrasah Aliyah Swasta Al-Washliyah 22 Tembung. Teacher pedagogical competence is a very important aspect in the success of the learning process because it is directly related to the teacher's ability to understand student characteristics, design learning, implement appropriate teaching strategies, and conduct effective learning outcome evaluations. In the context of madrasah education, the head of the madrasah has a significant responsibility not only as an administrative leader but also as an academic supervisor who plays a role in nurturing, directing, and continuously developing the professionalism of teachers. This research aims to describe the process of implementing clinical supervision by the head of the madrasah, identify the obstacles that arise in its application, and analyze its impact on the improvement of teachers' pedagogical competence. The research method used is a qualitative method with a descriptive approach, while data collection techniques are carried out thru observation, interviews, and documentation. The data obtained are systematically analyzed to gain an in-depth understanding of the implementation of clinical supervision in the madrasah. The research results show that clinical supervision plays an important role in encouraging teachers to be more professional, innovative, and reflective in carrying out their teaching. Thru this supervision, teachers are expected to enhance their understanding of students, develop better learning tools, and implement learning strategies that meet the demands of 21st-century education. In addition, clinical supervision also helps create a positive, open, and mutually supportive work culture in the madrasah environment. Therefore, clinical supervision by the head of the madrasah becomes one of the relevant strategies to improve the quality of education and overall learning quality.